Comparison of metal alkoxide initiators in the ring-opening polymerization of caprolactone - Meelua W. (2014)
Four metal tert-butoxides, namely: aluminum(III) tert-butoxide, Al(Ot-C 4H 9) 3, tin(II) tert-butoxide, Sn(Ot-C 4H 9) 2, titanium(IV) tert-butoxide, Ti(Ot-C 4H 9) 4, and lithium tert-butoxide, Li(Ot-C 4H 9), were used as initiators in the bulk ring-opening polymerization (ROP) of ε-caprolactone (CL). The polymerizations were carried out at 120 °C for 72 hrs. It was found that the Al(Ot-C 4H 9) 3 only partially dissolved in the CL monomer and gave a low % conversion. The Li(Ot-C 4H 9) initiator did not dissolve and gave no polymerization. In contrast, the Sn(Ot-C 4H 9) 2 initiator dissolved completely, albeit very slowly, and gave a high % conversion. The Ti(Ot-C 4H 9) 4 initiator was by far the easiest and quickest to dissolve and also gave a high % conversion. Consequently, Ti(Ot-C 4H 9) 4-initiated polymerization was studied further by dilatometry at 120 °C. From the kinetic results, a first-order rate constant, k p, of 0.120 l mol -1 min -1 was obtained. © (2012) Trans Tech Publications.